The complete air fryer cookbook over 100 easy, energy-efficient recipes for every meal. - ElNaggar, Jennette (New York, NY DK, 2023)
"The air fryer has taken household kitchens across the world by storm. This handy kitchen appliance makes cooking our favorite foods quicker, easier, cheaper and even healthier. From healthier versions of fried favorites to whole roast dinners, impressive vegetarian mains, crunchy snacks and baked treats, the air fryer will make your time in the kitchen a stress-free and mess-free experience. Now a popular trend on TikTok and social media, air fryer recipes continue to go viral--from cheesecakes to cheese toasties, corn on the cob to the quickest pakoras. Despite its name, the air fryer does not "fry" things; it bakes them, and it bakes them fast--the results are not only delicious but economical and energy-efficient"--
Includes index.
Keywords: Hot air frying; Quick and easy cooking; Cookbooks; Recipes